Myosins: a superfamily of molecular motors - Coluccio, Lynne M. (Advances in experimental medicine and biology, 2020)
Introduction -- Myosin Structure -- Cargo Binding by Unconventional Myosins -- Cryo-EM of Actin-Myosin Structures -- Small Molecule Effectors of Myosin Function -- Single-Molecule Biophysical Techniques to Study Actomyosin Force Transduction -- High-Speed Atomic Force Microscopy to Study Myosin Motility -- How Myosin 5 Walks Deduced from Single-Molecule Biophysical Approaches -- How Actin Tracks Affect Myosin Motors -- Myosins in the Nucleus -- Myosins in Cytokinesis -- Myosins and Disease -- Myosins and Hearing -- The Actomyosin Systems in Apicomplexa -- Approaches to Identify and Characterise MYO6-Cargo Interactions -- Class IX Myosins: Motorized RhoGAP Signaling Molecules -- Myosin X -- Myosin XVI -- Myosin XVIII -- Myosin XIX.